2023
DOI: 10.3390/molecules28155883
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of Perilla frutescens in Cancer Treatment

Abstract: Perilla frutescens is an annual herb of the Labiatae family and is widely grown in several countries in Asia. Perilla frutescens is a plant that is used medicinally in its entirety, as seen in its subdivision into perilla seeds, perilla stalks, and perilla leaves, which vary more markedly in their chemical composition. Several studies have shown that Perilla frutescens has a variety of pharmacological effects, including anti-inflammatory, antibacterial, detoxifying, antioxidant, and hepatoprotective. In the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…Its leaves, stems, and seeds can be used as medicine and food. These parts exhibit various pharmacological activities, such as anti-inflammatory, anti-infection, antioxidant, detoxifying, and hepatoprotective activities [27]. Therefore, perilla has been extensively studied in the field of medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its leaves, stems, and seeds can be used as medicine and food. These parts exhibit various pharmacological activities, such as anti-inflammatory, anti-infection, antioxidant, detoxifying, and hepatoprotective activities [27]. Therefore, perilla has been extensively studied in the field of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, perilla has been extensively studied in the field of medicine. Many studies have investigated the anticancer activity of perilla and demonstrated its in vitro antitumor function in multiple cancers, including lung, colon, breast, and liver malignancies [27]. In this study, we explored the potential of perilla phenols for use in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous types of extracts and components have been identified from this plant to date, each comprising a specific portfolio of biochemical activities and cytotoxic effects. A recent systematic review outlined 14 classes of Perilla frutescens active constituents: alkaloids phenylpropane, terpenoids, polyphenol compounds, flavonoids, anthocyanins, coumarins, carotenoids, neolignans, fatty acids, tocopherols, phytosterols, glucosides and peptides [3]. These classes reunite a plethora of compounds that have antitumoral effects by modulating various elements of the metabolic pathways or intercellular interactions such as reactive oxidative species (ROS), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), phosphoinositide 3-kinase/protein kinase B (PI3K/AKT), c-Jun N-terminal kinases (JNK), yes-associated protein/WW domain-containing transcription factor (YAP/TAZ), etc.…”
Section: Introductionmentioning
confidence: 99%
“…These classes reunite a plethora of compounds that have antitumoral effects by modulating various elements of the metabolic pathways or intercellular interactions such as reactive oxidative species (ROS), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), phosphoinositide 3-kinase/protein kinase B (PI3K/AKT), c-Jun N-terminal kinases (JNK), yes-associated protein/WW domain-containing transcription factor (YAP/TAZ), etc. [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These medicines offer numerous benefits, including high safety levels, minimal side effects, flexible dosage forms, good patient compliance, and the ability to target precancerous lesions (Hou and Jiang, 2013;Jiang et al, 2023;Zhong et al, 2023). Recent studies have confirmed the anticancer properties of extracts and purified bioactive monomer components present in various medicinal and edible Chinese medicines (Huang et al, 2023). When used in combination with other chemotherapeutic drugs, these Chinese medicines have shown the ability to enhance drug efficacy, mitigate adverse reactions, overcome drug resistance, and notably enhance patients' quality of life (Chen G. Q. et al, 2023;Lu et al, 2023).…”
mentioning
confidence: 99%